2016
DOI: 10.1016/j.bbrep.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane temperature gradients and multiple cell permeabilization induced by low peak power density femtosecond lasers

Abstract: Calculations indicate that selectively heating the extracellular media induces membrane temperature gradients that combine with electric fields and a temperature-induced reduction in the electropermeabilization threshold to potentially facilitate exogenous molecular delivery. Experiments by a wide-field, pulsed femtosecond laser with peak power density far below typical single cell optical delivery systems confirmed this hypothesis. Operating this laser in continuous wave mode at the same average power permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Subsequent molecular dynamics simulations showed that adding a temperature gradient to an electric pulse could induce pore formation in a lipid bilayer that did not occur in the absence of the temperature gradient [22]. Because of the short duration of the laser pulses used in wide illumination (diameter ≈ 50 µm IR radiation), we previously assessed the feasibility of cell membrane temperature gradients as a potential mechanism for the observed cell membrane temperature gradients [30]. Despite using similar peak powers and pulse durations as standard optoinjection lasers, the power densities for the wide field illumination study were three orders of magnitude lower due to the substantially larger illumination area (≈2500 µm 2 compared to ≈4 µm 2 for standard optoinjection).…”
Section: Theoretical Interpretation Of Results and Possible Mechanism...mentioning
confidence: 99%
“…Subsequent molecular dynamics simulations showed that adding a temperature gradient to an electric pulse could induce pore formation in a lipid bilayer that did not occur in the absence of the temperature gradient [22]. Because of the short duration of the laser pulses used in wide illumination (diameter ≈ 50 µm IR radiation), we previously assessed the feasibility of cell membrane temperature gradients as a potential mechanism for the observed cell membrane temperature gradients [30]. Despite using similar peak powers and pulse durations as standard optoinjection lasers, the power densities for the wide field illumination study were three orders of magnitude lower due to the substantially larger illumination area (≈2500 µm 2 compared to ≈4 µm 2 for standard optoinjection).…”
Section: Theoretical Interpretation Of Results and Possible Mechanism...mentioning
confidence: 99%
“…If such cells are preserved for further research or other uses, some caution must be exercised. In this respect, it has been published that low average power fs pulses are more than capable of porating cells, which totally preserved their viability but, nevertheless, made them to incorporate molecules from their surroundings (e.g., propidium iodide) [115]. The authors hypothesize that thermoelastic pulses are the source of this mild poration.…”
Section: Thermal Damage and Stress In Optical Tweezersmentioning
confidence: 99%
“…It should be emphasized that upon application of femtosecond laser pulses, in addition to ablation, plasmonic photoionization [27] as well as thermal effects have also been described. A comparison of high repetition infrared laser pulses (1.55 µm) with cw laser irradiation of the same wavelength and average power showed that in the first case a temperature gradient was generated which was more favorable to permeabilization of cell membranes [28].…”
Section: Mechanismsmentioning
confidence: 99%